A Systematic Review of AI-Powered Tools in English Language Learning for Vocational Students - Dewantara, Kadek Andre Karisma; Laksana, I Putu Yoga; Saraswati, Ni Putu Ritra Trees Ari Kartika Hadi (International Journal of Natural Science and Engineering, 2024)
Vocational education emphasizes the development of practical skills aligned with industry needs. In today's digital era, English proficiency combined with the ability to adapt to technological advancements such as Artificial Intelligence (AI) is essential. AI-powered tools have begun to transform English language learning by offering personalized, adaptive, and interactive experiences. This systematic review aims to examine and synthesize the characteristics of AI-powered tools and their implementation in English language learning for vocational students, focusing on how these technologies support communication, industry-specific language use, and learner autonomy. This systematic review follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to ensure a comprehensive and transparent review process. Data were gathered through searches in electronic databases including Scopus, ERIC, Google Scholar, and Web of Science using keywords such as “AI in language learning,” “vocational students,” “ESP,” and “English learning technology.” After screening based on inclusion and exclusion criteria, 20 studies published between 2018 and 2024 were selected for analysis. A narrative synthesis was used to extract and organize key themes. The review identified the following characteristics of AI-powered tools used in vocational English education: real-time feedback, adaptive content delivery, speech recognition for speaking practice, and chatbot-based conversation simulation. These tools were mostly applied through mobile apps, web platforms, and LMS integration. The outcomes showed positive impacts on students’ speaking fluency, vocabulary acquisition, motivation, and engagement. AI-powered tools offer significant potential for enhancing English language learning in vocational settings by providing personalized and flexible learning pathways.